Chiral γ‐Lactams by Enantioselective Palladium(0)‐Catalyzed Cyclopropane Functionalizations. (12th August 2015) - Pedroni, Julia; Cramer, Nicolai
Abstract Cyclopropanes fused to pyrrolidines are important structural features found in a number of marketed drugs and development candidates. Typically, their synthesis involves the cyclopropanation of a dihydropyrrole precursor. Reported herein is a complementary approach which employs a palladium(0)‐catalyzed CH functionalization of an achiral cyclopropane to close the pyrrolidine ring in an enantioselective manner. In contrast to aryl–aryl couplings, palladium(0)‐catalyzed CH functionalizations involving the formation of C(sp3)C(sp3) bonds of saturated heterocycles are very scarce. The presented strategy yields cyclopropane‐fused γ‐lactams from chloroacetamide substrates. A bulky Taddol phosphonite ligand in combination with adamantane‐1‐carboxylic acid as a cocatalyst provides the γ‐lactams in excellent yields and enantioselectivities.